2009
DOI: 10.2214/ajr.08.2214
|View full text |Cite
|
Sign up to set email alerts
|

Air Embolism and Needle Track Implantation Complicating CT-Guided Percutaneous Thoracic Biopsy: Single-Institution Experience

Abstract: The incidence of air embolism with clinical symptoms and needle track implantation complicating percutaneous thoracic biopsy is more frequent than the previously reported rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 25 publications
3
49
1
Order By: Relevance
“…The incidence of hemorrhage was 1% (95% CI 0.9-1.2%) and blood transfusion was required in 18% [4]. Although the frequency of fatal complications like pleural dissemination and air embolism was low, these were also reported [38]. No complications directly caused by VBN were reported, and the VBN complication rate was equivalent to that on conventional bronchoscopy [39] and far lower than that on TTNA, which is a marked advantage.…”
Section: Advantages Of Vbnmentioning
confidence: 99%
“…The incidence of hemorrhage was 1% (95% CI 0.9-1.2%) and blood transfusion was required in 18% [4]. Although the frequency of fatal complications like pleural dissemination and air embolism was low, these were also reported [38]. No complications directly caused by VBN were reported, and the VBN complication rate was equivalent to that on conventional bronchoscopy [39] and far lower than that on TTNA, which is a marked advantage.…”
Section: Advantages Of Vbnmentioning
confidence: 99%
“…The complications of TFNAB in lungs include pneumothorax, haemoptysis, air embolism and needle tract metastasis [1,3,5,11,12]. In TFNAB using a C-arm CBCT system by Jin et al [7], the overall complication rate was reported as 38%, which comprised pneumothorax (25.4%), haemoptysis (14.1%) and chest pain (1.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Common complications include pneumothorax and pulmonary hemorrhage, both of which are known to be generally self-resolving with no clinical intervention required. Air embolism is a potentially life-threatening but extremely rare complication, with an estimated incidence of 0.02-0.06% (1,2); however, the incidence of air embolism is considered to be underestimated due to undiagnosed asymptomatic patients (3)(4)(5). The present study reports a case of air embolism in the coronary and spinal arteries, which, following a CT-guided PCNB of the lung, resulted in sudden mortality.…”
Section: Introductionmentioning
confidence: 71%